SPATIAL NARRATIVE OF PLACE NAMING IN TANGERANG: REPRESENTATION OF CINA’S BENTENG CULTURAL IDENTITY (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
An ethnic experiences changes and faces challenges from time to time. A cultural ethnicity may strengthen its existence from time to time or maybe more marginalized and 'lost'. Cina Benteng as one of native of Tangerang deals with these challenges that affects their existence and identity. It is estimated that Cina Benteng stepped in Tangerang at 1600’s as part of Laksamana Cheng Ho arrival in Banten. Cina Benteng takes roles in all historical stories during the era of Sumedang Larang’s kingdom, Colonial era, and after the independence of Indonesia. However nowadays phenomenon, as the massive number of migrants enter Tangerang, the existence of Cina Benteng are being questioned. To deal with this changes and challenges, an ethnic can use a cultural marker strategy related to the concept of space. The process of cultural proclamation describes a symbolic demarcation of what can be accessed by outsiders and what remains the privilege of an ethnic within the scope of cultural space (Christomy, 2018). The concept of space in the study of cultural studies is close to the aspect of place naming of certain space. At the language level, place naming describe the meaning of names or places, explore social, cultural and historical information. At the level of social practice, it’s describes the form of social practice, how space is constructed and interpreted by other people / groups. In this paper, space as a form of cultural marker is seen from the spatial narrative method spoken by an a member of ethnic, Cina Benteng. The spatial narrative which is chosen, is a narrative related to folklore or historical stories related to certain place naming. The purpose of this paper is to find out how space and place are constructed by ethnic Chinese Benteng through narrative and what the implications are for those involved in this construction. This paper will use a qualitative approach by utilizing ethnographic methods. This paper will utilize cultural studies theory such as the theory of place and space by James Fox (2006), spatial narrative theory by Christomy (2018), and Labov theory of Narrative Inquiry (2006). In the first part of this paper, the writer presents a scientific synthesis related to spatial representation from the point of view of cultural sciences. In the second part, this paper carried out discussions and conclusions related to the problem of the research.